Correlation of Husband and Family Support on the Success of Breastfeeding in the Working Area of the Sabrang Health Center - Indah Oktaviani (LPPM Universitas dr. Soebandi, 2023)
Background: Breast milk is breast milk that can meet the needs of babies aged 0-6 months. The ingredients in breast milk can produce antibodies, improve psychomotor development, and strengthen the bond between mother and baby. The low coverage of exclusive breastfeeding in the Sabrang Community Health Center working area is 16.9%. To achieve exclusive breastfeeding, breastfeeding mothers need support, especially the support of husbands and families who play an important role in the smooth breastfeeding and breastfeeding process. This research method uses a cross sectional method. Sampling uses quota sampling. The sample consisted of 30 respondents. Statistical analysis uses the Chi-square test. Analysis of the relationship between husband and family support on the success of breastfeeding in the Sabrang Community Health Center work area. Statistical test results were obtained using Chi-Squre calculations using SPSS 25, the results for person Chi-Squre (2-tailed) were 0.002 and 0.000 < 0.05. So Ho is rejected and Ha is accepted, which means there is a relationship between husband and family support for the success of breastfeeding